Implementation of lean manufacturing indicators: overall equipment efficiency and the six major losses of maintenance at Pack-Isi company - Morales Cruz, Erick Uriel (2025)
The purpose of this study was to assess both the overall equipment efficiency (OEE) and the six major maintenance losses in a pelletizing machine owned by a plastics company. An improvement plan was established through the development of a root cause analysis. The investigation was conducted between August 5 and 10, 2024. The results indicated an OEE below 80 %, not reaching world class status. It was found that unscheduled and minor stops were responsible for the reduction in global efficiency. The root cause analysis allowed us to establish actions that reduced downtime, unscheduled stoppages, and out-of-specification products, thus increasing quality and productivity.